Development Mind Mapping-Based Pocket Book Learning Media to Improve Student Learning Outcomes - Sakinah, Nurul Hidayati; Yuliati, Lia; Utama, Candra (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The aim of the study was to produce a pocket book based on mind mapping for grade IV elementary schools on the theme of always saving energy which was tested for a valid level in terms of expert validation, interesting in terms of student response questionnaires and effective in terms of pre-test and post-test. Experiments were carried out using non-equivalent control group design and using a research and development model with a 4D development model including Defining, Designing, Developing and Deploying. Data collection using the method of observation, questionnaires, interviews and documentation. The results of this research, it can be said that the category is very valid, very interesting and the post-test score is greater than the pre-test score. The use of pocket book learning media based on mind mapping can improve student learning outcomes grade IV.